1993
DOI: 10.7863/jum.1993.12.11.659
|View full text |Cite
|
Sign up to set email alerts
|

Fetal echocardiography: factors that influence imaging of the fetal heart during the second trimester of pregnancy

Abstract: When the fetal heart cannot be imaged during the second trimester, these factors should be identified. Using data from this study, the gestational age at which the highest probability of imaging the heart can be determined if the thickness of the adipose tissue and a history of lower abdominal surgery are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 7 publications
4
72
1
Order By: Relevance
“…Our purpose in choosing this approach was to limit our study only to the postprocessing part of the examination. As volume acquisition can be affected by many factors such as operator skills, gestational age at examination, maternal body habitus, fetal position, fetal movement, fetal breathing, and amniotic fluid volume [54,55,58,69], it would be difficult to control for these factors when analyzing the data. Volume acquisition has been previously studied by Viñ als et al [55], who examined volume datasets of 100 consecutive fetuses between 18 and 37 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Our purpose in choosing this approach was to limit our study only to the postprocessing part of the examination. As volume acquisition can be affected by many factors such as operator skills, gestational age at examination, maternal body habitus, fetal position, fetal movement, fetal breathing, and amniotic fluid volume [54,55,58,69], it would be difficult to control for these factors when analyzing the data. Volume acquisition has been previously studied by Viñ als et al [55], who examined volume datasets of 100 consecutive fetuses between 18 and 37 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, sonographic visualization of fetal structures is adversely affected by the size of the body fat layer and thus the degree of maternal obesity. 14,15 The impact of obesity on the quality of prenatal ultrasound examination was described by Wolfe et al, 16 in 1990, who found a greater risk for suboptimal visualization only when body mass index (BMI, kg/m 2 ) was above the 90th percentile. Although this finding (a decreased ability to visualize fetal structures with maternal obesity) was described over 14 y ago, quantification of this effect based on the severity of obesity using National Institute of Health (NIH) guidelines 17 is not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Schwärzler et al 26 and DeVore et al 41 found a direct relationship between visualization and GA, which in our case was not significant. However, fetal movements, the maternal habitus, and uterine fibroids were not associated with poorer sensitivity.…”
Section: Exploration Timementioning
confidence: 32%
“…Our algorithm was feasible in 81.5% of cases, which was similar to other algorithms for evaluation of the fetal heart (Table 7). 3,24,41 Comparisons, however, are difficult, given that those algorithms are not based on exactly the same views as our algorithm and often do not take the exploration time into account.…”
Section: Use Of Complementary Techniques: Color Doppler Imagingmentioning
confidence: 99%